Rapidly Resolving Nonalcoholic Marchiafava-Bignami Disease in the Setting of Malnourishment After Gastric Bypass Surgery - Moshe Bachar MD; Eduard Fatakhov MD; Christopher Banerjee MD, MPH; Nathan Todnem MD (SAGE Publishing, 2018)
Objectives. We describe a rare case of nonalcoholic Marchiafava-Bignami disease (MBD) in the setting of malnourishment after gastric bypass. Methods. A 44-year-old nonalcoholic Caucasian woman with malnutrition after gastric bypass presented with 2 weeks of weakness. The patient acutely became stuporous. Brain magnetic resonance imaging showed lesions in the corpus callosum and internal capsules consistent with MBD. After 10 days of treatment, the patient had resolution of her encephalopathy with return to baseline mental function, with radiological improvement. Results. MBD is a rare neurological disorder seen in alcoholics and can rapidly progress to coma or death. Our patient was successfully treated with a regimen typically used in alcoholics. We discuss the relevant literature supporting this regimen. Conclusions. This case demonstrates that since the pathophysiological etiology of the disease is malnutrition, MBD patients can be effectively treated with this regimen regardless of the underlying cause.